The Wiley handbook of social studies research - Manfra, Meghan McGlinn; Bolick, Cheryl Mason (Wiley handbooks in education)
"The Wiley Handbook of Social Studies Research is a wide-ranging resource on the current state of social studies education. This timely work not only reflects on the many recent developments in the field, but also explores emerging trends. This is the first major reference work on social studies education and research in a decade. An in-depth look at the current state of social studies education and emerging trends. Three sections cover: foundations of social studies research, theoretical and methodological frameworks guiding social studies research, and current trends and research related to teaching and learning social studies. A state-of-the-art guide for both graduate students and established researchers. Guided by an advisory board of well-respected scholars in social studies education research"--